Finnish flow diverter study: 8 years of experience in the treatment of acutely ruptured intracranial aneurysms - Alpay Kemal; Hinkka Tero; Lindgren Antti E; Isokangas Juha-Matti; Raj Rahul; Parkkola Riitta; Sinisalo Matias; Numminen Jussi; Pienimäki Juha-Pekka; Saari Petri; Seppänen Janne; Palosaari Kari; et al. (BMJ Publishing Group, 2022)
Background: Flow diversion of acutely ruptured intracranial aneurysms (IAs) is controversial due to high treatment-related complication rates and a lack of supporting evidence. We present clinical and radiological results of the largest series to date.
Methods: This is a nationwide retrospective study of acutely ruptured IAs treated with flow diverters (FDs). The primary outcome was the modified Rankin Scale (mRS) score at the last available follow-up time. Secondary outcomes were treatment-related complications and the aneurysm occlusion rate.
Results: 110 patients (64 females; mean age 55.7 years; range 12-82 years) with acutely ruptured IAs were treated with FDs between 2012 and 2020 in five centers. 70 acutely ruptured IAs (64%) were located in anterior circulation, and 47 acutely ruptured IAs (43%) were blister-like. A favorable functional outcome (mRS 0-2) was seen in 73% of patients (74/102). Treatment-related complications were seen in 45% of patients (n=49). Rebleeding was observed in 3 patients (3%). The data from radiological follow-ups were available for 80% of patients (n=88), and complete occlusion was seen in 90% of aneurysms (79/88). The data from clinical follow-ups were available for 93% of patients (n=102). The overall mortality rate was 18% (18/102).
Conclusions: FD treatment yields high occlusion for acutely ruptured IAs but is associated with a high risk of complications. Considering the high mortality rate of aneurysmal subarachnoid hemorrhage, the prevention of rebleeding is crucial. Thus, FD treatment may be justified as a last resort option.